Occupational Physical Hazards and Safety Practices at Dental Clinics - Alamri, Abdulaziz; ElSharkawy, Mahmoud Fathy; Alafandi, Dalal (European Journal of Dentistry, 2022)
Objective Worldwide, dentistry is known as a high-level occupational hazard profession. Dental staff is usually exposed to several types of hazards which include chemical agents, physical, psychological stress, and workplace violence, biological and ergonomics. The objectives of this paper were to assess levels of occupational hazards and evaluate safety practices at dental clinics.Materials and Methods At several dental clinics, levels of noise, lighting, and radiation were measured by recommended instruments and the safety practice was evaluated using a validated and reliable questionnaire (during 3 months of 2020).Results The mean levels of noise ranged between 46.3 and 67.2 dB, while the noise dose percent (noise exposure level) ranged between 60.7 and 77.6 dB. The mean levels of lighting ranged from 236.3 lux in the X-ray room to 1,080.3 lux in the dental laboratory. The mean levels of radiation ranged from 7.8 to 12.1 µrem. The mean levels of the three physical hazards were lower than their permissible levels at all locations.Conclusion Levels of noise in dental clinic were affected by the change in the work activities, while this factor has no effect on the levels of lighting and radiation except for certain processes. The demographic variables such as gender, specialization, and the average number of patients showed a significant association with physical hazards, safety practices, while there was no significant association with radiation protection.
Keywords: noise; radiation; lighting; dental clinic; safety practice; maximum permissible value